Las obligaciones en moneda extranjera en el proyecto de código civil - Paolantonio, Martín E. (2012)
This work analyzes Section 765 of the Draft Civil Code, which deals with\nforeign currency obligations. The rule proposed by the Executive Branch returns to the\noriginal system of the Civil Code, which did not consider foreign currency obligations\nas monetary obligations. The proposed text reopens interpretive questions hotly debated\nin the doctrine and jurisprudence until 1991, without any apparent advantage to be\nexpected from the change. On the contrary, the uncertainty generated by the proposed\nrule, coupled with the prohibition of contractual indexing, will undoubtedly result in\nhigher transaction costs in private contracting, and unnecessary litigation